Risk of second cancer following radiotherapy for prostate cancer: a population-based analysis. Issue 1 (December 2017) - Hegemann, Nina-Sophie; Schlesinger-Raab, Anne; Ganswindt, Ute; Hörl, Claudia; Combs, Stephanie; Hölzel, Dieter; Gschwend, Jürgen; Stief, Christian; Belka, Claus; Engel, Jutta
Abstract Background To investigate the risk of second cancer and radiation induced second cancer following prostate cancer radiotherapy. Methods We compared men with radiotherapy only with those treated with radical prostatectomy only and those with radiotherapy after radical prostatectomy. Cumulative incidences of second cancers were calculated. Cox analyses were performed to identify determinants influencing second cancer incidence. Results Nineteen thousand five hundred thirty eight patients were analyzed. Age and median follow-up differed significantly with radiotherapy only patients having the highest median age (70.3 years) and radical prostatectomy only patients the longest median follow-up (10.2 years). Ten-year cumulative incidence of second cancer was 15.9%, 13.2% and 10.5% for patients with radiotherapy only, radiotherapy after radical prostatectomy and radical prostatectomy only (p < 0.0001). Increasing age and belonging to the radiotherapy only group were associated with a higher risk of second cancer—no significant increase was seen in radiotherapy after radical prostatectomy patients. A significantly higher rate of smoking related malignancies, like lung, bladder and non-melanoma skin cancer, was seen in radiotherapy only patients. Conclusions No clear increase in radiation induced second cancer was found in patients after radiotherapy for prostate cancer. Whereas the rate of second cancer was increased in radiotherapy only patients, no such increase was seen in patients with radiotherapy after radical prostatectomy. The increase of second cancer following radiotherapy only is highly likely to reflect advanced age and lifestyle habits and comorbidities.